SEMANTIC PECULIARITIES AND RELATIONSHIP OF PHRASEOLOGY (Web of Teachers: Inderscience Research, 2024)
This article explores the semantic peculiarities of phraseology and its relationship with language structure and meaning. The author highlights key characteristics of phraseological units, including idiomaticity, fixedness, and semantic unity. The article emphasizes the significance of understanding phraseological units in uncovering the intricacies of language use and communication. The author emphasizes the idiomatic nature of phraseological units, noting that their meanings often cannot be deduced from the individual meanings of their constituent words. Additionally, the article discusses the fixedness of phraseological units, highlighting their resistance to modification or substitution. The semantic unity of phraseological units is also highlighted, emphasizing how the meaning of the whole unit emerges from the interaction of its constituents.